PENGARUH KEGIATAN BERKEBUN TERHADAP KECERDASAN NATURALIS PADA ANAK USIA 5-6 TAHUN - Rina Oktavia (Jurnal CARE (Children Advisory Research and Education), 2022)
This study aims to determine whether or not there is an influence between gardening activities on the naturalist intelligence of children aged 5-6 years. The subjects in this study were children aged 5-6 years in TK/RA Cimanggu District, Pandeglang-Banten. The method used in this research is quantitative experiment, namely quasi-experimental design with nonequivalent control group design. The sample selected after the researcher was RA Hayati Nufus as the experimental group and TK Al-Quran Bhakti Wanita as the control group. With the number of each student, which is 15 children. The data testing technique in this study uses instrument validity and reliability testing, normality test, homogeneity test, hypothesis testing (t-test) which is processed using the help of the IBM SPSS 22.0 for windows program. Based on the results of research which shows that the natural intelligence of children aged 5-6 years who receive treatment or treatment with gardening activities is very influential on the natural intelligence of children aged 5-6 years in TK/RA Cimanggu District, Pandeglang-Banten. This can be seen from the significant value. Based on the results of the t test calculation, it is obtained that the Sig 2 tailed value in the experimental class is in this study H0 is rejected and H1 is accepted.